Civil law problems of contractual relations in the framework of interaction between detectives and law enforcement agencies - D. A. Dudkin (Гуманитарные и юридические исследования)
The relevance of the topic under consideration is due to the fact that in modern conditions, in order to combat administrative and criminal offenses, along with bodies operating within the framework of public legal regulation, various types of entrepreneurial activities operating within the framework of private legal means of legal regulation continue to develop.The interaction of detectives and law enforcement agencies in the Russian Federation acts as an integral element of the mechanism for implementing the law enforcement function of our country. This is primarily due to the fact that both state (represented by law enforcement agencies) and non-state (represented by private detectives) bodies act as subjects that implement the human rights (law enforcement) function of the state. The relevance of the topic under consideration is beyond doubt in view of the aggravated political situation at the international level that has developed during the special military operation conducted by the Russian Federation. The current foreign policy situation has turned the idea of the unshakable priority of international law, the norms and provisions of which are simply not taken into account and ignored by a number of countries. In the current situation, law enforcement agencies do not always have the opportunity to carry out their activities outside the jurisdiction of Russia, falling under the sanctions of unfriendly states, while a private detective has a free hand since they are a business entity and act primarily in the interests of the customer of these services.The article highlights the problematic issues of the implementation of contractual relations arising   within the framework of interaction between detectives and law enforcement agencies. On the basis of this, civil law problems are identified that prevent them from exercising their human rights function, the signs and conditions of concluding a confidential cooperation agreement between the parties within the framework of current legislation are considered.